Identitas nasional: A hybrid systematic literature review dan analisis bibliometrik - HAQIQI, MUH RIZAL (Maliki Interdisciplinary Journal, 2025)
The formation of national identity has become an increasingly urgent issue amid the currents of globalization, transnational ideologies, and the fragmentation of identity in contemporary society. This study aims to map the development of national identity research using a hybrid approach that combines a Systematic Literature Review (SLR) and bibliometric analysis. Data were collected from the Dimensions database, covering 74 articles published in the past year. Utilizing VOSviewer software, the bibliometric analysis identified dominant keywords, thematic linkage networks, and publication trends. The results indicate that the themes of cognitive flexibility, identity inclusiveness, latent class analysis, mainstream cultural group, majority group acculturation, and cultural identity occupy dominant positions in the literature related to national identity. However, the existence of topic fragmentation suggests a need for a more integrative conceptual approach. Meanwhile, the SLR findings reveal that most studies still emphasize psychological aspects such as pride and emotional attachment. To address this gap, the study proposes a new indicator called Civic Engagement Practices, which reflects citizens’ active involvement in socially and nationally relevant activities. These findings are expected to broaden theoretical understanding and offer practical contributions for designing educational policies, social integration strategies, and more contextual national identity narratives.